2010
DOI: 10.2174/1876386301003010003
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Importance of Neuron-Satellite Glia Interactions within Trigeminal Ganglia in Craniofacial Pain

Abstract: Pain in the head and face, which can be very severe and debilitating, often involves activation of trigeminal ganglion nerves. The craniofacial symptoms can manifest as acute or transient conditions such as toothaches and headaches, or can transform into more chronic conditions such as migraine, rhinosinusitis, temporomandibular joint (TMJ) disorder, or trigeminal neuralgia. Traditionally, it is known that peripheral tissue injury or inflammation leads to excitation of trigeminal nerves that release inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 111 publications
0
23
0
Order By: Relevance
“…The movement of the dye from neuronal cell bodies to the satellite glial cells likely involved the formation of gap junctions between these two cells. This type of neuron-glia coupling within the trigeminal ganglion has been observed following peripheral inflammation or in response to inflammation and nerve injury (Cherkas et al, 2004, Vit et al, 2008, Durham and Garrett, 2010, Villa et al, 2010). Importantly, increased signaling between neurons and glia with the ganglion is associated with development and maintenance of peripheral sensitization of nociceptive neurons.…”
Section: Discussionmentioning
confidence: 90%
“…The movement of the dye from neuronal cell bodies to the satellite glial cells likely involved the formation of gap junctions between these two cells. This type of neuron-glia coupling within the trigeminal ganglion has been observed following peripheral inflammation or in response to inflammation and nerve injury (Cherkas et al, 2004, Vit et al, 2008, Durham and Garrett, 2010, Villa et al, 2010). Importantly, increased signaling between neurons and glia with the ganglion is associated with development and maintenance of peripheral sensitization of nociceptive neurons.…”
Section: Discussionmentioning
confidence: 90%
“…In the trigeminal ganglion (TG), gap junctions in satellite cells contribute to neuron-satellite signaling and may result in spread of neural activation to V3 cells that do not ordinarily receive input from the injured site (Durham and Garrett, 2010). An increase in the apparent size receptive fields may also reflect ectopic discharges from primary afferents in V3, resulting from ligation of V2 (Wall and Gutnick, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Satellite cells in the DRG show increased gap junction coupling after injection of complete Freund’s adjuvant (CFA) into the hindpaw, an effect that parallels a reduction in the pain threshold52,53. In the trigeminal ganglion, injection of the retrograde tracer True Blue into the temporomandibular joint capsule leads to accumulation of the dye in SGCs after injection of capsaicin into the temporomandibular joint54. Importantly, there is no gap junction coupling between DRG neurons or between neurons and SGCs in the absence of noxious stimulation53.…”
Section: Inflammation and Peripheral Nociceptor Sensitizationmentioning
confidence: 99%
“…Thalokoti et al 55 showed that activation of the sensory neurons that innervate the mandibular territory led to pain-related cellular changes not only in neurons and SGCs of the mandibular division but also in the maxillary and ophthalmic divisions of the trigeminal ganglion. This cross-excitation within the sensory ganglion provides a mechanism for extraterritorial pain that occurs outside the injured dermatome54.…”
Section: Inflammation and Peripheral Nociceptor Sensitizationmentioning
confidence: 99%